Chromium treatment decreases the sensitivity of 5-HT2A receptors. - Attenburrow, M; Odontiadis, J; Murray, B; Cowen, P; Franklin, M (2002)
RATIONALE: Recent case series suggest that chromium picolinate in doses of 400 microg daily may have antidepressant properties, perhaps through increasing the peripheral availability of tryptophan for brain serotonin (5-HT) synthesis. OBJECTIVES: To determine the effects of chromium treatment on plasma tryptophan availability and on brain 5-HT function in human and animal models. METHODS: We studied the effects of short-term chromium supplementation on plasma concentrations of tryptophan and other large neutral amino acids. Brain 5-HT function was assessed by measuring the corticosterone/cortisol response to the 5-HT precursor, 5-hydroxytryptophan (5-HTP), a response believed to be mediated via indirect activation of 5-HT(2A) receptors. RESULTS: In rats, chromium increased peripheral and central tryptophan availability and elevated brain 5-HT content. Changes in peripheral tryptophan availability were not seen in humans but in both rats and humans, chromium lowered the cortisol response to challenge with 5-HTP. CONCLUSIONS: Chromium can modify brain 5-HT function in humans and animals, perhaps by altering the sensitivity of central 5-HT(2A) receptors.